Bilateral Simultaneous Rhegmatogenous Retinal Detachment following Laser in situ Keratomileusis - Yumusak, Erhan (Case Rep Ophthalmol, 2016)
A 21-year-old woman developed simultaneous rhegmatogenous retinal detachment after laser in situ keratomileusis (LASIK) in both eyes. She underwent pars plana vitrectomy surgery combined with endolaser photocoagulation and silicone oil tamponade in the right eye. A week later, pneumatic retinopexy was done in the left eye. As the retinal tear did not seal, 360° scleral buckling surgery was performed and retina was attached. Bilateral simultaneous rhegmatogenous retinal detachment after LASIK for correction of myopia can be a serious complication. Patients should be informed about the possibility of this complication.